Workplace Flexibility : Realigning 20th-Century Jobs for a 21st-Century Workforce - Schneider, Barbara; Christensen, Kathleen (Book collections on Project MUSE., 2015)
Although today's family has changed, the workplace has not--and the resulting one-size-fits-all workplace has become profoundly mismatched to the needs of an increasingly diverse and varied workforce. As changes in the composition of the workforce exert new demands on employers, considerable attention is being paid to how workplaces can be structured more flexibly to achieve the goals of employers and employees. Workplace Flexibility brings together sixteen essays authored by leading experts in economics, demography, political science, law, sociology, anthropology, and management. Collectively, they make the case for workplace flexibility, as well as examine existing business practices and public policy regarding flexibility in the United States, Europe, Australia, and Japan. Workplace Flexibility underscores the need to realign the structure of work in time and place with the needs of the changing workforce. Considering the positive and negative consequences for employer and employee alike, the authors argue that, although there is not an easy solution to creating and implementing flexibility practices--in the United States or abroad--redesigning the workplace is essential if today's workers are effectively to meet the demands of life and work and if employers are successfully able to attract and retain top talent and improve performance.